The Influence Of Service Quality and Lifestyle On Purchase Decisions Using Shopee Paylater In Bandar Lampung - Salma, Aulia Mutiara; Ekawati, Evi; Anggraeni, Erike (LPPM Institut Nasional Laa Roiba Bogor, 2024)
The development of the digital world is driving transformation in the world of retail and finance. Currently, e-commerce has presented a variety of payment methods with the aim of ensuring consumer comfort and convenience in carrying out transactions. One of the trending payment features is Shopee Paylater. The aim of this research is to analyze the influence of service quality and lifestyle on purchasing decisions using Shopee Paylater in Bandar Lampung. The method in this research uses a quantitative approach. The data source in this research is primary data obtained from 114 respondents using Shopee Paylater in Bandar Lampung using accidental sampling technique. The data analysis used is multiple linear regression analysis using SPSS version 22 software. Based on the results of this research, it shows that the regression results for the service quality variable show a positive correlation of 0.262. Apart from that, the results of the T test show that tcount 2.630 > ttable 1.65833, meaning that the service quality variable influences purchasing decisions using Shopee Paylater. And the regression results for lifestyle variables show a positive correlation of 0.370. Apart from that, the results of the T test show that tcount 3.710 > ttable 1.65833, meaning that lifestyle variables influence purchasing decisions using Shopee Paylater.